Chainsaw blue ; Simeon Banahaw ; For the people [videorecording] - Lazaro, Cheche; Banahaw, Simeon (The Probe Team, 1989)
Tackles logging and its effects on environment ; a painter who draws inspiration from the mystical legends of Mt. Banahaw in Quezon City Province; and the massacre of "civilians" in Paombong, Bulacan when the military claims that those killed were NPA's or NPA symphatizers.